Job Insecurity, Procedural Justice and Downsizing Survivor Affects - Lopez-Bohle, S (Routledge, 2021)
The current study developed and tested a mediation model that accounts for the procedural justice in the relationship between the perception of job insecurity and affect. We used a sample of 681 workers, from four private enterprises in the retail industry in Chile, who survived an organizational downsizing process. The hypotheses were tested by using structural equation modeling (SEM). The results indicated that the perception of job insecurity and employees’ negative affects was partially mediated by procedural justice. However, the relationship between job insecurity and employees’ positive affects was totally mediated by procedural justice. Therefore, such results suggest that it is important during a downsizing process for companies to implement actions to enhance job security in order to develop adequate affect among survivors. Furthermore, it is also seemingly crucial that justice should be an important issue in the downsizing process, and that the company should develop actions that reflect the perception of procedural justice throughout the process. Thus, this research provides evidence that it is useful to simultaneously consider procedural justice and stress reactions in a downsizing process, since neither are independent variables. © 2018 Informa UK Limited, trading as Taylor & Francis Group.